FUV VARIABILITY OF HD 189733. IS THE STAR ACCRETING MATERIAL FROM ITS HOT JUPITER? - Pillitteri, I.; Maggio, A.; Micela, G.; Sciortino, S.; Wolk, S. J.; Matsakos, T. (The Astrophysical journal, 2015)
ABSTRACT Hot Jupiters are subject to strong irradiation from their host stars and, as a consequence, they do evaporate. They can also interact with the parent stars by means of tides and magnetic fields. Both phenomena have strong implications for the evolution of these systems. Here we present time-resolved spectroscopy of HD 189733 observed with the Cosmic Origins Spectrograph on board Hubble Space Telescope (HST). The star has been observed during five consecutive HST orbits, starting at a secondary transit of the planet ( ). Two main episodes of variability of ion lines of Si, C, N, and O are detected, with an increase of line fluxes. The Si iv lines show the highest degree of variability. The far-ultraviolet variability is a signature of enhanced activity in phase with the planet motion, occurring after the planet egress, as already observed three times in X-rays. With the support of MHD simulations, we propose the following interpretation: a stream of gas evaporating from the planet is actively and almost steadily accreting onto the stellar surface, impacting at ahead of the subplanetary point.